2015
DOI: 10.1007/s10453-015-9382-6
|View full text |Cite
|
Sign up to set email alerts
|

Airborne fungal richness: proxies for floral composition and local climate in three sites at the El Palmar National Park (Colón, Entre Ríos, Argentina)

Abstract: The analysis of the content of the airborne mycofloras from three Tauber traps (monthly from March 2011 to March 2013) located at a dense palm (EP3), a grassland (EP2) and a mixed area (EP1, composed of grassland, palms and wetland communities) was carried out. Their affinity with the floral composition of each site and a possible influence of local atmospheric conditions on total fungal spore richness were tested. This analysis allowed the recognition of 82 fungal morphotypes as a whole. The cluster analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
1
0
1
Order By: Relevance
“…Flowers are the origin of seed development and dispersal and also contain a large microbiome ( 78 ), and Nelson showed that microbes associated with flowers are an important source of seed-associated microbes ( 21 ). Furthermore, the floral nectar, which comprises secondary metabolites, particularly sugars and amino acids, can provide a source of energy and available carbon for seed-borne microbial growth ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…Flowers are the origin of seed development and dispersal and also contain a large microbiome ( 78 ), and Nelson showed that microbes associated with flowers are an important source of seed-associated microbes ( 21 ). Furthermore, the floral nectar, which comprises secondary metabolites, particularly sugars and amino acids, can provide a source of energy and available carbon for seed-borne microbial growth ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…Varios de los sustratos sobre los que ha sido registrada H. celastri son abundantes en la localidad en estudio (Bahía Blanca) donde han sido introducidos como ornamentales, por ejemplo, Lantana y algunas especies de Pinus. Si bien estas especies arbóreas son también comunes en la flora de otras ciudades del país, la presencia de Helicogermslita no ha sido mencionada en los escasos estudios aerobiológicos previos que consignan en forma detallada las esporas de origen fúngico (Mallo et al, 2011;Nuñez-Otaño et al, 2015).…”
Section: Discussionunclassified